TECHNOLOGY OF GIVING SOFTNESS TO KNITTED FABRICS - F. S. Usmanova; J. J. Ergashova; N. D. Nabiyev (Web of Journals Publishing, 2024)
Perforation of the fabric during the sewing of ready-made garments from knitted fabrics is one of the problematic defects. This defect occurs when the threads on the knitted fabric break. In textile materials, thread breakage is characterized by complete or partial breakage of individual threads in the fabric during sewing. The porosity of the fabric can be divided into visible and invisible types, which can be eliminated by processing different compositions. This paper explores the application of soft cationic surfactants, amino modified silicone oil - 350, amino modified silicone oil - 200, DMC amino modified silicone oil - 350 and silicone-based softeners to knitted fabrics. Based on the results of experiments on the effect of variable process factors on the perforation of knitted fabrics in the sewing process, it is recommended to use imported silicone-based softener and local amino-modified silicone oil-350. According to the results of the experiment, the technological procedure and composition of the final finishing process of "softening" of knitted fabrics with selected softeners were developed. it has been shown that it is expedient to heat-treat a fabric soaked in a softener solution for 5 minutes at a temperature of 1400C.
Keywords: Softening, hardness, porosity, thread breakage, finishing, heat treatment, knitting, surfactant.